1989
DOI: 10.1056/nejm198905253202105
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Placebo-Controlled Trial of Oral Acyclovir for the Prevention of Cytomegalovirus Disease in Recipients of Renal Allografts

Abstract: Cytomegalovirus is a major viral pathogen in patients who undergo renal transplantation, and cytomegalovirus disease is difficult to treat. We therefore conducted a randomized, placebo-controlled, double-blind trial of acyclovir for the prevention of cytomegalovirus disease in recipients of renal allografts from cadavers. Acyclovir was given orally in doses of 800 to 3200 mg per day, according to the patients' estimated level of renal function. Patients took the first dose of either acyclovir or placebo six ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
151
4
2

Year Published

1990
1990
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(162 citation statements)
references
References 28 publications
5
151
4
2
Order By: Relevance
“…21 We have recently decreased the length of time antibiotics are continued from 5 days to 48 hours in the face of a lack of data supporting any benefit from the longer time period. Certainly the role of viral prophylaxis has been well documented, 13,15,16 and we believe that aggressive fungal prophylaxis is warranted in these high-risk patients as well.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…21 We have recently decreased the length of time antibiotics are continued from 5 days to 48 hours in the face of a lack of data supporting any benefit from the longer time period. Certainly the role of viral prophylaxis has been well documented, 13,15,16 and we believe that aggressive fungal prophylaxis is warranted in these high-risk patients as well.…”
Section: Discussionmentioning
confidence: 90%
“…The optimal prophylaxis against CMV infection after solid organ transplantation has been controversial, and several different combinations of ganciclovir, both intravenous and oral; oral acyclovir; and human anti-CMV immunoglobulin have been described with varying effectiveness. [12][13][14][15][16] We used a short course of intravenous ganciclovir followed by high-dose oral acyclovir for 3 months without regard to serological status. Our incidence of invasive CMV disease was only 14%.…”
Section: Discussionmentioning
confidence: 99%
“…Interesting pharmacokinetic studies were conducted to show that the peak level of aciclovir was about 25 J..lM and the trough 18 J..lM; renal transplant patients thus had higher levels than found in normals, presumably because their renal insufficiency was delaying excretion of the drug. Despite these high levels, the values did not approach the mean ID 5 0 for the CMV strains isolated from the same patients, which was around 63 J..lM (Balfour et a/., 1989). The fact that the drug was shown to improve CMV disease compared to placebo suggests that the viruses in the patients did respond to the drug and leads to the inevitable conclusion that the Reed etal., 1990GCV Goodrich et al, 1991IFN Cheeseman et al, 1979Hirsch et al, 1983Lui et al, 1992ACV Prentice et al, 1994Balfour et al, 1989Ig Metselaar et al, 1989GCV Winston etal., 1993Merigan, 1992Goodrich, et al, 1993 Treatment Pre-emptive Suppression Prophylaxis Table 4.…”
Section: Treatment Strategiesmentioning
confidence: 93%
“…The incidence and severity of CMV disease are also influenced by the amount of immunosuppression used (188)(189)(190)(191). Chemoprophylaxis for CMV (with acyclovir, ganciclovir, valacyclovir and/or intravenous immunoglobulin) has been shown to be effective in large, randomized controlled trials (192)(193)(194)(195)(196)(197)(198). A meta-analysis of controlled trials also concluded that antiviral agents (acyclovir or ganciclovir) were effective in preventing CMV infection in solid-organ transplant recipients (199).…”
Section: Rationalementioning
confidence: 99%